Hubungan Sikap, Media Konseling dan Bimbingan Terhadap Perilaku Kemandirian Ibu Nifas Dalam Melakukan Perawatan Tali Pusat: Relationship between Attitudes, Counseling Media and Guidance on Independent Behavior of Postpartum Mothers in Performing Umbilical Cord Care - Suci Rahayu (Indonesian Scholar Journal of Nursing and Midwifery Science, 2021)
Introduction: Umbilical cord care is an act of care and cleaning of the umbilical cord, and try to keep the umbilical cord in a dry and clean condition to prevent infection. The purpose of the study was to determine the relationship between attitudes, media counseling, and guidance on independent behavior of postpartum mothers in performing umbilical cord care at the Surade Health Center, Sukabumi Regency in 2021. Methods: The design of this study was descriptive-analytic with a cross-sectional approach. In this study, the population of postpartum mothers on the 7th to 9th day in August 2021 at the Surade Health Center was based on data on delivery plans in August 2021 as many as 72 people. The sample in this study amounted to 72 respondents using a total population sampling technique. Researchers used the Chi-Square test. Results: Based on the results of the statistical test, it is known that the attitude variable has a P-value of 0.000, the media counseling variable has a P value of 0.003 and the guidance variable has a P-value of 0.001. Discussion: There is a relationship between attitudes, counseling, and guidance on the independent behavior of postpartum mothers in umbilical cord care at the Surade Health Center, Sukabumi Regency in 2021. Suggestions for the Public Health Centre to socialize with the community, especially postpartum mothers regarding central care.